THE IMPACT OF INFLATION AND INTEREST RATES ON EXCHANGE RATES IN IRAQ - Lect. Dr. Jabbar Saadoon Darag (American Journals, 2024)
The research included the concept of the exchange rate and the factors affecting it, as well as inflation in terms of the concept and the factors affecting it, and interest rates in terms of the concept and factors affecting the interest rate, for the period (2004-2023). Data was used through the Central Bank of Iraq. An autoregressive model was studied. Through the ARDL program, the results were that there was a relationship between the independent variables, represented by inflation and interest rates, and the dependent variable, represented by the exchange rate, through the results of the aforementioned model.
Keywords: Exchange rate, interest rates, inflation, ARDL